Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fendo.2022.965167
|View full text |Cite
|
Sign up to set email alerts
|

Possible roles of exercise and apelin against pregnancy complications

Abstract: The prevalence of maternal obesity during pregnancy is associated with the risk of gestational diabetes, preeclampsia, and cardiomyopathy. Environmental factors such as active lifestyles and apelin may lead to beneficial changes. In rats, apelin and exercise (45 to 65% VO2max for 6 to 9 weeks) during pregnancy increase brown adipose tissue (BAT) proteins such as Cidea, Elovl3, UCP1, PRDM16, and PGC-1α in males and females fetuses, while white adipose tissue (WAT) is reduced. In humans and animals, apelin and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 151 publications
0
4
0
Order By: Relevance
“…The cfDNA profile in C EPE model contained eight genes, of which pTSS coverages of FOSL2 , CAMKK2 , CCND1 , ITPR1 , PRKACB , WNT7B , CACNB2 and NRF1 genes were stably differential between pregnant women with early-onset PE and healthy controls. CAMKK2 , CCND1 , ITPR1 , PRKACB and WNT7B genes were enriched in more than two pathways associated with PE, including “Hedgehog signaling pathway” ( 35 ), “Hippo signaling pathway” ( 36 ), “AMPK signaling pathway” ( 37 ), “Apelin signaling pathway” ( 38 ), “Autophagy” ( 39 ), “Oxytocin signaling pathway” ( 40 ), “Wnt signaling pathway” ( 41 ) and “VEGFA-VEGFR2 signaling” ( 42 ). The AMPK signaling pathway has been repeatedly reported to be associated with PE based on omics data ( 37 , 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…The cfDNA profile in C EPE model contained eight genes, of which pTSS coverages of FOSL2 , CAMKK2 , CCND1 , ITPR1 , PRKACB , WNT7B , CACNB2 and NRF1 genes were stably differential between pregnant women with early-onset PE and healthy controls. CAMKK2 , CCND1 , ITPR1 , PRKACB and WNT7B genes were enriched in more than two pathways associated with PE, including “Hedgehog signaling pathway” ( 35 ), “Hippo signaling pathway” ( 36 ), “AMPK signaling pathway” ( 37 ), “Apelin signaling pathway” ( 38 ), “Autophagy” ( 39 ), “Oxytocin signaling pathway” ( 40 ), “Wnt signaling pathway” ( 41 ) and “VEGFA-VEGFR2 signaling” ( 42 ). The AMPK signaling pathway has been repeatedly reported to be associated with PE based on omics data ( 37 , 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Apelin is also involved in glucose homeostasis, and higher levels of apelin were observed in obesity and T2DM [ 91 ]. In humans and animals, apelin is a stimulant of the glucose transporters (GLUT1/2/4) expression in the muscle and adipose tissue via the PI3K/Akt and AMPK pathways [ 92 ]. It has been noticed that the placenta produces significant amounts of apelin, and apelin levels in the foetal blood are higher than in mothers [ 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, they emphasized that the role of the apelin/aPJ system in placental endothelial and vascular function should be confirmed in future studies (lim et al, 2013). moreover, the necessity of examining the APLN/APJ axis, especially in the first, second, and third trimesters, with a focus on temporal change, is also emphasized in the literature (alizadeh Pahlavani, 2022). Studies in mice have shown that apelin can increase glucose utilization (Dray et al, 2008).…”
Section: Discussionmentioning
confidence: 99%